PRIORITY DIRECTIONS FOR THE DEVELOPMENT OF SCIENTIFIC KNOWLEDGE IN THE CRIMINAL LEGAL PROTECTION OF THE RIGHTS OF INTELLECTUAL PROPERTY - Лихова, Софія Яківна; Станкевич, Юрій Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the task of scientific research is to determine the priority of applying the methodology of knowing the characteristics of forms of criminal law protection of intellectual property rights. Some issues of improving the legal regulation of sectoral legislation are considered. Methods of research: the comparative legal method of scientific knowledge, general scientific and special methods is used in the work. Results: the key issues and methods of legal regulation of criminal law protection of intellectual property are determined. Discussion: international normative acts, national legislation, positions of individual scholars.